Odpowiedzialność człowieka za przyrodę w ujęciu Bazylego Wielkiego - Ewa Osek (Vox Patrum, 2005)
According to St. Basil the human condition and the State of nature are always the same. The histories of the mankind and natural world are closely connected, because of his conception of the nature, conceived as the whole of which a man is a part. St. Basil basing himself on the Scriptures divides the word history into three stages: 1) the Paradise age, 2) the times after the Fali, and 3) eschatological timeless future.